Retrospective analysis of exercise capacity in patients with coronary artery disease after percutaneous coronary intervention or coronary artery bypass graft - Ying Li; Xue Feng; Biyun Chen; Huaping Liu (Elsevier, 2021)
Objectives: To describe the current state of exercise capacity as well as to identify its predictors in patients with coronary artery disease (CAD) following percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG) in the mainland of China. Methods: A retrospective study design was employed. We evaluated 230 CAD patients following PCI or CABG in a cardiac rehabilitation center from January 2019 to October 2019. The patients were referred to undergo incremental cardiopulmonary exercise testing with a cycle ergometer. The Zung Self-Rating Anxiety Scale and the Zung Self-Rating Depression Scale were used to evaluate patients' mental health. Statistical analysis was performed using the chi-square test, Fisher's exact test, t-test, Mann-Whitney U test, and binary logistic regression. Results: Among the 230 patients, 223 patients demonstrated reduced exercise capacity. Resutlts of the logistic regression analysis showed that anxiety (OR = 1.13, 95% CI 1.01-1.32, P = 0.029) was an independent risk factor for reduced exercise capacity in patients following the PCI or CABG. Conclusions: Exercise capacity of Chinese CAD patients after PCI or CABG was relatively poor. Alleviating symptoms of anxiety and making exercise prescriptions according to the results of the cardiopulmonary exercise test should be considered during the intervention to improve CAD patients' exercise capacity.